A randomized clinical trial investigating the efficacy of targeted nutrition as adjunct to exercise training in COPD. Issue 5 (12th June 2017) - van de Bool, Coby; Rutten, Erica P.A.; van Helvoort, Ardy; Franssen, Frits M.E.; Wouters, Emiel F.M.; Schols, Annemie M.W.J.
Abstract: Background: Evidence regarding the efficacy of nutritional supplementation to enhance exercise training responses in COPD patients with low muscle mass is limited. The objective was to study if nutritional supplementation targeting muscle derangements enhances outcome of exercise training in COPD patients with low muscle mass. Methods: Eighty‐one COPD patients with low muscle mass, admitted to out‐patient pulmonary rehabilitation, randomly received oral nutritional supplementation, enriched with leucine, vitamin D, and omega‐3 fatty acids (NUTRITION) or PLACEBO as adjunct to 4 months supervised high intensity exercise training. Results: The study population (51% males, aged 43–80) showed moderate airflow limitation, low diffusion capacity, normal protein intake, low plasma vitamin D, and docosahexaenoic acid. Intention‐to‐treat analysis revealed significant differences after 4 months favouring NUTRITION for body mass (mean difference ± SEM) (+1. 5 ± 0. 6 kg, P = 0. 01), plasma vitamin D (+24%, P = 0. 004), eicosapentaenoic acid (+91%, P < 0. 001), docosahexaenoic acid (+31%, P < 0. 001), and steps/day (+24%, P = 0. 048). After 4 months, both groups improved skeletal muscle mass (+0. 4 ± 0. 1 kg, P < 0. 001), quadriceps muscle strength (+12. 3 ± 2. 3 Nm, P < 0. 001), and cycle endurance time (+191. 4 ± 34. 3 s, P < 0. 001). Inspiratory muscle strength only improved in NUTRITION (+0. 5 ± 0. 1 kPa, P = 0. 001) and steps/day declined in PLACEBO (−18%, P = 0. 005). Conclusions: High intensity exercise training is effective in improving lower limb muscle strength and exercise performance in COPD patients with low muscle mass and moderate airflow obstruction. Specific nutritional supplementation had additional effects on nutritional status, inspiratory muscle strength, and physical activity compared with placebo.